Longitudinal monitoring of somatic genetic alterations in circulating cell‐free DNA during treatment with epidermal growth factor receptor–tyrosine kinase inhibitors. Issue 1 (10th September 2019) - Iwama, Eiji; Sakai, Kazuko; Hidaka, Noriko; Inoue, Koji; Fujii, Akiko; Nakagaki, Noriaki; Ota, Keiichi; Toyozawa, Ryo; Azuma, Koichi; Nakatomi, Keita; Harada, Taishi; Hisasue, Junko; et al.
Abstract : Background: The aim of this study was to evaluate the potential of liquid biopsy for prediction of the efficacy of epidermal growth factor receptor (EGFR)–tyrosine kinase inhibitor (TKI) treatment and for assessment of the changes in genetic alterations during such treatment. Methods: Plasma samples were prospectively collected from non–small cell lung cancer patients with EGFR ‐activating mutations during EGFR‐TKI treatment until disease progression and were analyzed for such mutations with droplet digital polymerase chain reaction and for other somatic alterations with next‐generation sequencing. Results: One hundred patients, including 87 who were EGFR‐TKI naïve, were enrolled. Median progression‐free survival was significantly shorter for EGFR‐TKI–naïve patients with EGFR ‐activating mutations detected in plasma at baseline than for those without them (7.9 vs 19.0 months; P  < .001), with the values being significantly longer for initially positive patients who became negative for these mutations at 12 or 24 weeks than for those who remained positive. An increase in the number of alleles positive for EGFR ‐activating mutations in plasma during treatment was associated with disease progression, with a hazard ratio of 4.72 (95% CI, 2.07‐10.79; P  < .001) for EGFR‐TKI–naïve patients showing an increase within 36 weeks. For 55 patients with available samples, the total number of somatic alterations (other than activating mutations or T790M of EGFR ) in plasma was higher at disease progression than at baseline (33 vs 19; P  = 0.04). Conclusion: Liquid biopsy shows potential for prediction of EGFR‐TKI efficacy and elucidation of clonal tumor evolution during targeted therapy. Abstract : The presence or an increase in the number of alleles positive for epidermal growth factor receptor ( EGFR )–activating mutations in plasma before or during EGFR–tyrosine kinase inhibitor treatment is a negative predictive biomarker for such treatment. Liquid biopsy has the potential to elucidate the clonal evolution of tumors during targeted therapy.